The Effect of Acupressure on Reducing the Intensity of Primary Dysmenorrhea Among Nursing Students at Tadulako University in Palu City - Mariani, Andi; Fauzan, Fauzan; Fahrurezi, Fahrurezi; Fitriani, Fitriani; Herman, Herman (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Dysmenorrhea is a common condition characterized by menstrual pain experienced by adolescent girls, which can significantly affect their quality of life. Acupressure therapy is considered effective in alleviating pain intensity. This study aims to evaluate the impact of acupressure on reducing dysmenorrhea intensity among students of Akper Untad in Palu City. Objective: This research aims to analyze the effect of acupressure therapy on primary dysmenorrhea intensity in female students. Methods: This study employed a quasi-experimental design with a pre-test and post-test approach. A total of 47 female students participated as respondents. Pain intensity was measured using a 0-10 scale before and after acupressure treatment. Data analysis was performed using the Paired T Test. Results: The findings indicate that the average dysmenorrhea intensity before treatment was 7.77, which decreased to 3.00 after treatment. Statistical analysis revealed a p-value of 0.000, indicating a significant effect of acupressure on reducing dysmenorrhea intensity. Conclusion: Acupressure therapy is effective in reducing primary dysmenorrhea intensity among female students at Akper Untad in Palu City. This study provides evidence that acupressure can be a valuable non-pharmacological intervention for managing dysmenorrhea.